Observational astronomy : a very short introduction - Cottrell, Geoff (Oxford : Oxford University Press, 2023)
Unlocking the secrets of the Universe involves the critical application of the laws of physics to the observations. This Very Short Introduction describes how we are turning observations into knowledge and how theory, in turn, is inspiring new observations.
Also issued in print: 2023.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on July 5, 2023).
Keywords: Astronomy -- Observations; Science; Astronomy, space & time